2021
DOI: 10.1080/21655979.2021.2008217
|View full text |Cite
|
Sign up to set email alerts
|

Hsa_circ_0030586 promotes epithelial–mesenchymal transition in prostate cancer via PI3K-AKT signaling

Abstract: Circular RNAs (CircRNAs) gain importance as regulatory molecules in prostate cancer (PCa), but molecular mechanism of most circRNAs in pathogenesis of PCa remains to be studied. This study aimed to explore the role of hsa_circ_0030586 in PCa. Gene Expression Omnibus database (GSE77661) was used to screen out candidate circRNAs. Quantitative real-time PCR was used to verify the relative expressions of circRNAs, miRNAs, and genes in PCa cells. A CCK-8 assay was used to evaluate the cells’ proliferation. Transwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Circ0016068 sequesters miR-330-3p and releases BMI-1 to enhance PCa cell proliferation, migration, and invasion, as well as xenograft tumor metastasis. Circ0030586 was found to be highly expressed in PCa cells using the GEO database [ 170 ]. Knockdown of circ0030586 in PC3 cells inhibited PCa cell proliferation, migration and invasion, and resulted in significant up-regulation of E-cadherin and significant down-regulation of p-AKT/AKT, IKKα, PIK3CB, and Twist.…”
Section: Expression and Biological Function Of Circrnas In Urinary Sy...mentioning
confidence: 99%
“…Circ0016068 sequesters miR-330-3p and releases BMI-1 to enhance PCa cell proliferation, migration, and invasion, as well as xenograft tumor metastasis. Circ0030586 was found to be highly expressed in PCa cells using the GEO database [ 170 ]. Knockdown of circ0030586 in PC3 cells inhibited PCa cell proliferation, migration and invasion, and resulted in significant up-regulation of E-cadherin and significant down-regulation of p-AKT/AKT, IKKα, PIK3CB, and Twist.…”
Section: Expression and Biological Function Of Circrnas In Urinary Sy...mentioning
confidence: 99%
“…Of note, our previous studies (16,17) confirmed that the circ_0026782, circ_0004826, circ_0077837, circ_0001946, and circ_0030586 were significantly downregulated, whereas circ_0003141 and circ_0008039 was dramatically upregulated in BCa vs. paired non-tumorous tissues, which were consistent with our circRNA sequencing data; besides, circ_0077837, circ_0004826 and circ_0030586 served as tumor suppressors and prognosis predictors in BCa. Additionally, some circRNA among our sequencing such as circ_0008039, circ_0000745, circ_000074, circ_0077837, circ_0030586, and circ_0001946, etc, were also closely associated with malignant biological behavior of other cancer types (37)(38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, circSPECC1 promoted the proliferation and migration of LNCaP prostate cancer cells by affecting EMT. Similarly, hsa_circ_0030586 is significantly overexpressed in prostate cancer cells, and downregulation of hsa_circ_0030586 can reduce the proliferative, migratory, and invasive ability of prostate cancer cells and further inhibit their EMT [ 18 ]. In addition, hsa_circ_0001085 may indirectly regulate the PI3K-Akt and TGF- β signaling pathways through hsa_miR-196b-5P and the MAPK signaling pathway through hsa_miR-451A, thereby playing a regulatory role in the EMT-induced model of prostate cancer cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%